Homogeneous earthquake catalogue for Northeast region of India using robust statistical approaches. Issue 2 (15th December 2017) - Pandey, Auchitya Kumar; Chingtham, Prasanta; Roy, P. N. S.
ABSTRACT: Regular seismic hazard assessment requires essentially an updated and refined homogenous earthquake catalogue for the study region. Here, we have compiled the earthquake data for Northeast region of India in a chronological order from International Seismological Centre and Global Centroid Moment Tensor databases during the period 1 January 1900 to 31 April 2016. For this purpose, the regression techniques such as least square (SR), inverse least square (ISR), orthogonal (OR) and generalized orthogonal (GOR) which is the best one, out of that are employed for converting different types of magnitude scales, such as surface-wave magnitude ( MS ), body-wave magnitude ( mb ) and local magnitude ( ML ) into a single homogenized moment magnitude, MW . The homogenized catalogue is then treated with 'runs test' to estimate p -value of 0.8421 which suggest no spurious reporting on the catalogue. The prepared catalogue has also been declustered using standard procedure. Furthermore, the magnitude of completeness for space and time with 90% confidence level has been achieved. The seismicity parameters, namely magnitude of completeness MC, a -value and b -value are found to be 4.6, 7.50 and 0.95(±0.023), respectively. The observed low b -value implies that the study region is tectonically very active with the presence of asperity.